Comparision of DNA extraction methods to detect trace amounts of tree nut allergens in chocolates - Costa, Joana (2014)
Food-induced allergies represent an emerging problem of food safety. Thus, to safeguard the health of sensitised consumers, food ingredients that may cause allergic reactions should be properly labelled and possible cross-contamination should be avoided. Among food allergies, abnormal immunological responses towards tree nuts are pointed as a frequent source of serious atypical reactions, in which the hypersensitivities associated to almond and hazelnut ingestion are considered dangerous due to their incidence and severity [1 ,2]. Although immunological methods have been used for the direct detection of the almond and hazelnut allergens with high sensitivity, these assays are susceptible to cross-reactivity with other tree nuts